Possible Reversal of Carbon Tetra Chloride-induced Liver Fibrosis in Sprague Dawley Rats treated with Stromal Vascular Fraction and Activated Platelet Rich Plasma (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Stromal vascular fraction (SVF) is considered a promising source of stem cells, but potential of treatment of damaged liver has not been fully explored. Aim: In this study, we sought to evaluate the hepato-regenerative effect of SVF combined with activated platelet rich plasma (aPRP) on carbon tetrachloride (CCl4) induced hepatic injury in Sprague Dawley (SD) rats. Liver fibrosis was induced using CCl4 in 30 SD rats. Sixteen rats survived and were divided into two groups – control and treated. SVF and aPRP were prepared by standard methods from three normal donor rats. Combination SVF-aPRP was administered intravenously via the lateral tail vein in treated group animals, on Day 0, 7 and 14. Normal saline of same dose volume was administered to the control group. AST and ALT levels were monitored throughout the study duration of 28 days. Gross and histopathological analysis of liver was performed post sacrifice on Day 28. Decrease in the ALT/AST levels over the duration of study was observed in both control and treated groups, with a statistically significant reduction in AST/ALT levels between Control ad Treated groups on Day 28. Gross morphological evaluation, fibrosis and cirrhosis grades also showed reduction between control and treated groups. Observations of enzyme levels, gross and histopathological analyses revealed a reduction in severity of liver fibrosis in the treated group. However, we have identified additional parameters that need to be evaluated to corroborate these research findings.